Micro-milling of Ti-6Al-4V material - Nurul Aini, Yunus (2016)
Micro-end milling is one of the promising methods for rapid fabrication of features with 3D complex shapes. However, controlling the micro-end milling process to obtain the desired results is much harder compared to that of macro-end milling due to the size effect and uncontrollable factors. The problem is much pronounced when workpiece material is a difficult-to-process material such as titanium-based alloys which are widely used as material of choice for medical implants. This research is about the effect of machining parameters in terms of feed rate and depth of cut with constant spindle speed in wet and dry condition on Ti-6Al-4V's surface roughness using micro-milling process. This experiment was design using Design of Experiment (DOE) method and few numbers of experiments were constructed. The results show that feed rate is the most critical parameter which effect on surface roughness during machining process followed by depth of cut. Dry condition shows better surface quality compared to wet condition.